2011
DOI: 10.1142/s0218863511006133
|View full text |Cite
|
Sign up to set email alerts
|

OPTICAL LIMITING IN TeO2ZnO GLASS FROM Z-SCAN TECHNIQUE

Abstract: TeO 2– ZnO glasses were prepared by conventional melting procedure, and their optical properties were determined. In the present work, we measured the optical non-linearity of the glass. The measurement was carried out using a single beam z-scan technique given by Sheike Bahe et al. We could observe that the material exhibits reverse saturable absorption, and the effective nonlinear absorption coefficients are numerically evaluated. This study is important in identifying the nonlinear material as a Reverse Sat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Notably, the sharp decreasing trend of T min and the extremely low T min (≈20%) at high radiation can be clearly observed. Two‐photon absorption (TPA) model can be used to fit above changes and the normalized transmittance T ( Z ) can be described by Equations and T Z=m=0q0Zmm+11.5q0= βI0[]1normalexpα0L[]1+Z/Z02α0where α 0 and β are the linear absorption coefficient and the TPA coefficient, respectively, L is the thickness of the sample, Z 0 = kω 2 is the diffraction length of beam, k = 2π/λ is the wave number, and ω is the beam waist radius. Based on these relations, the β parameter which directly reflects the TPA property can be calculated to be 3.065 cm GW −1 , which is much larger than that of the other classic nonlinear candidates such as 0.565 cm GW −1 for TeO 2 –Bi 2 O 3 –WO 3 system, 1.428 cm GW −1 for Bi 2 O 3 –B 2 O 3 –TiO 2 system, and 1.483 cm GW −1 for TeO 2 –TiO 2 system .…”
Section: Resultsmentioning
confidence: 51%
“…Notably, the sharp decreasing trend of T min and the extremely low T min (≈20%) at high radiation can be clearly observed. Two‐photon absorption (TPA) model can be used to fit above changes and the normalized transmittance T ( Z ) can be described by Equations and T Z=m=0q0Zmm+11.5q0= βI0[]1normalexpα0L[]1+Z/Z02α0where α 0 and β are the linear absorption coefficient and the TPA coefficient, respectively, L is the thickness of the sample, Z 0 = kω 2 is the diffraction length of beam, k = 2π/λ is the wave number, and ω is the beam waist radius. Based on these relations, the β parameter which directly reflects the TPA property can be calculated to be 3.065 cm GW −1 , which is much larger than that of the other classic nonlinear candidates such as 0.565 cm GW −1 for TeO 2 –Bi 2 O 3 –WO 3 system, 1.428 cm GW −1 for Bi 2 O 3 –B 2 O 3 –TiO 2 system, and 1.483 cm GW −1 for TeO 2 –TiO 2 system .…”
Section: Resultsmentioning
confidence: 51%
“…The authors observed that ESA was at the basis of the observed effect of RSA, resulting in OL. Furthermore, non doped TeO 2 –ZnO glass was also tested . This exhibited an OL threshold of 45 × 10 –3 J cm –2 at input laser power density of 81 × 10 –3 J cm –2 , and 160 × 10 –3 J cm –2 at input laser power density of 162 × 10 –3 J cm –2 .…”
Section: Inorganic Materialsmentioning
confidence: 99%
“…Such conducting amorphous layer can be of interest in many different applications e.g. in non linear optical material as a reverse saturation absorption based optical limiter [30].…”
Section: Experimental Techniquesmentioning
confidence: 99%